How does the Gender Difference in Willingness to Compete evolve with Experience? - Thomas Buser (Tinbergen Institute, 2016)
I study how gender differences in willingness to compete evolve over time in response to experience. Participants in a lab experiment perform the same real-effort task over several rounds. In each round, they have to choose between piece-rate remuneration and a winner-takes-all competition. At the end of each round, those who compete get feedback on the competition outcome. The main result is that women are much more likely than men to stop competing after a loss, which leads to the appearance of a significant gender gap in competitiveness even among those who are initially willing to compete. This gender effect is also present for high performers. In an additional experiment, I show that giving feedback to non-competers might further increase the gender gap in willingness to compete as men who initially choose not to compete react more strongly to positive feedback compared to women.
Keywords: C91; D03; J01; J16; 330; competitiveness; gender; feedback; career decisions; laboratory experiment